PENGARUH PENGEMBANGAN KARIER TERHADAP INTENSI TURNOVER DI PT BENUA PENTA GLOBAL MEDAN - Putra, Achmad Irvan Dwi; Lie, Velentina; Alvani, Shella (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
Every organization in general has a dependency on aspects of human resources. Organizations are required to obtain, develop, and maintain quality human resources in order to plan, do, and determine the realization of the goals of the organization. This study aims to determine the relationship between career development with turnover intentions. The hypothesis proposed in this study is that there is a negative relationship between career development and turnover intentions. The research subjects used in this study were employees of PT Benua Penta Global in Medan was 103 people selected by using total sampling. Analysis of the data used is to use Product Moment correlation through the help of SPSS 17 for Windows. The results of data analysis showed r = -0,299, and p = 0.002 (p <0.05) which shows that there is a negative relationship between career development and turnover intention. The results of this study indicate that the contribution (R2) given by career development variables to turnover intentions is 9 percent, while the remaining 91 percent is influenced by other factors.